The Analysis of Correlative Conjunctions Used in Undergraduate Students’ Research Articles - Yeni Savitri; Junaedi Setiyono; Sri Widodo (Scripta : English Department Journal, 2021)
This research belongs to qualitative research. The aims of this research are to identify the types of correlative conjunction and to explain their functions in students’ research articles. The data source of this research is students’ research articles written by undergraduate students of English Language Education Program at Purworejo Muhammadiyah University in the academic year of 2018/2019. In collecting the data, the researcher checked all the research articles published from August 2019 until December 2019. In analyzing the data, the researcher organized the data from the first correlative conjunction until the last correlative conjunction found in research articles; gave code for each of the correlative conjunctions; classified the correlative conjunctions based on the types: both__and, not only__but also, either__or, and neither__nor; classified the correlative conjunctions based on their functions in joining sentence elements such as words, phrases, and clauses; counted the data; discussed the finding; and drew conclusion and suggestion based on the data in this research. The result of this research shows that there are 91 correlative conjunctions found in 46 research articles: 39 both__and (42.86%), 40 not only__but also (43.96%), 8 either__or (8.79%), and 4 neither__nor (4.39%). There are 25 conjunctions connecting words (27.47%), 65 conjunctions connecting phrases (71.43%), and 1 conjunction connecting clauses (1.10%).